INTERPRETATION OF HEAVEN IN THE TAFSIR AL-AZHAR BY HAMKA AND ITS RELEVANCE TO EDUCATIONAL VALUES - Parwanto, Wendi; Yuliarto, Udi; Aydin, Muhammed (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2023)
Abstract Many researchers have conducted studies on Hamka. However, studies on the rationalization of the interpretation of verses about Heaven and tracing the causes of the rationalization of performance have yet to be carried out. Therefore, the researcher was interested in conducting this study further. The type of this research is library research with a descriptive-analytical method. The genealogical theory of Michel Foucault explains the genealogy of Hamka's interpretation of thought. The conclusion of this article explains that, Firstly, Hamka attempts to make a rational and contextual interpretation of the verses describing Heaven. With the method of sensible and contextual performance, the metaphysical and abstract nature of Heaven becomes easily understood by readers (society), moreover explained by Hamka in simple language and explanation. Secondly, Hamka's rationalist thinking and contextual typology of description were influenced by several factors, including his life experience as a preacher, writer, organization, and his teachers. Thirdly, Hamka's interpretation of the verses about Heaven accommodates educational values ​​between humans and God and also among humans.